95.1k views
5 votes
10x + 8 = 3(x – 2)
10x + 8 = 3x

User Alexx
by
4.7k points

1 Answer

5 votes

Answer:

x = -2

Explanation:

First off, you times everything and you get rid of the bracket:

So 3 times x gives 3x, and 3 times -2 is negative 6 (-6)

10x + 8 = 3x -6

Then you bring the alike variables to one side of the equation

Take away -3x from both sides and take away 8 from both sides

10x - 3x = -6 -8

Then you just divide 7 from both sides

7x = -14

x = -14/7

x = -2

:)))

User Sofiane Majdoub
by
5.2k points